A low data-rate fluorescence lifetime imaging system with CMM pre-processed in-pixel. (November 2017) - Xu, Jiangtao; Zhang, An; Gao, Zhiyuan; Nie, Kaiming; Qiao, Jun
Abstract: A low-data-rate implementation of fluorescence lifetime imaging based on pre-processing center of mass method (CMM) in pixel is proposed. The system utilizes gated ring oscillators (GROs) and two counters to integrate photon time-of-arrival. The electric states of GROs between two oscillations can be held and restored. Time quantization and integration can be flexibly realized by two counters. Each pixel includes a SPAD, quenching circuits, time-to-digital converters (TDCs), counters and registers. Pre-processing of CMM is implemented in pixel to reduce data rate and improve the frame rate. Estimating different theoretical lifetimes with software post calibrations, the system shows an estimation error below 2% within the solvable range under 1% excitation rate and 40 MHz synchronous clock. The power consumption of each pixel is 192.6 μW. The data rate per pixel is 0.01 Mbps and the maximum frame rate is 400 fps. Design of video-rate system with large SPAD array is practical to carry out.